Research of the gastronomic brand of Odesa and practical recommendations for solving key problems - Kharenko, Dmytro; Dyshkantiuk, Oksana; Salamatina, Svitlana; Khalilova-Chuvaeva, Iuliia; Kovalenko, Liliia (Technology audit and production reserves, 2018)
This work is aimed at studying the process of forming a gastronomic brand to enhance the attractiveness of the tourist destination. Formation of a competitive gastronomic brand is an effective strategy in the struggle for international markets, providing a stable tourist flow and economic development of the region. The object of research is the gastronomic brand of multicultural tourist destination on the example of the city of Odesa (Ukraine). One of the biggest problems in the formation of the gastronomic Odesa brand is the lack of interaction of its main components. In this process, the interaction should involve all stakeholders and market participants. In addition, the city of Odesa has not yet developed an effective strategy for the formation of a regional gastronomic brand. It is necessary to identify the main participants in the gastronomic life of the city, their role in shaping the brand and form a strategy for mutually beneficial development. As a result of the use of methods of content analysis and expert interviewing, it is concluded that the large unrealized potential of the gastronomic brand of Odesa, both internationally and nationally, is concluded. It is also found that restaurant business and gastronomic festivals are extremely important elements in the formation of the gastronomic brand as a source of gastronomic culture. The key issues related to the formation of the gastronomic brand of the city are identified. For their decision, the idea is put forward for the creation of gastronomic card-guides of the city of Odesa, which will inform tourists and residents of the city about the gastronomic life of the region. These information systems will allow all market participants to interact effectively with each other. The ways of forming a brand based on the cultural and culinary traditions of the city and region have also been developed. The practical value of the carried out research is that it can serve as the basis for further research and form an effective strategy to promote the city of Odesa as a tourist destination.